Penerapan Metode TOPSIS Terhadap Skala Prioritas Aspirasi Civitas Kampus UKRI - Novianti Indah Putri; Yogi Saputra; Faisal Aziz; Sigit Sugara; Kaka Sultan M Guteres (TEMATIK, 2024)
The campus community at the National University of the Republic of Indonesia has a fairly high level of criticism of the development of the campus itself, however, it turns out that the campus does not have sufficient media to accommodate the aspirations expressed by the campus community. Aspirations can be conveyed, but with a limited scale and time that also makes it difficult for campuses to make decisions that will later have an impact on the development of the National University of the Republic of Indonesia campus, therefore the TOPSIS method is here to make it easier for campuses to make decisions. The TOPSIS calculation refers to the alternative distances to the positive ideal solution and the negative ideal solution. From the results of calculations that have been normalized, the highest value has the right to get priority as the best solution, and conversely, the lowest value is not prioritized to be used as a reference in decision making.